2014
DOI: 10.1002/ajmg.a.36625
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to methotrexate and birth defects: A population‐based study

Abstract: Methotrexate is an anti-folate medication that is associated with increased risk of multiple birth defects. Using data from the National Birth Defects Prevention Study, a case-control study of major birth defects in the United States, we examined mothers exposed to methotrexate. The study population included mothers of live-born infants without major birth defects (controls) and mothers of fetuses or infants with a major birth defect (cases), with expected dates of delivery between October 1997 and December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 19 publications
1
29
0
2
Order By: Relevance
“…These compounds had ability to inhibit proliferation of the growth of cancer cells [9][10][11][12]. The other studies revealed that medicine which has inhibitory effects in proliferation such as methotrexate also gave similar abnormalities of intrauterine growth and significant weight loss in both human and animal experiments [19,20]. Besides external abnormalities, fetal bleeding was also found, which was hematoma (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds had ability to inhibit proliferation of the growth of cancer cells [9][10][11][12]. The other studies revealed that medicine which has inhibitory effects in proliferation such as methotrexate also gave similar abnormalities of intrauterine growth and significant weight loss in both human and animal experiments [19,20]. Besides external abnormalities, fetal bleeding was also found, which was hematoma (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Dr. Damkier and Dr. Kaplan [Damkier and Kaplan, this issue] for their interest in our recent manuscript [Dawson et al, ], and their comments on our presentation of data regarding birth defects in the children of mothers who reported preconceptional or prenatal exposure to methotrexate in the National Birth Defects Prevention Study.…”
Section: To the Editormentioning
confidence: 99%
“…A low dose of the folic acid antagonist methotrexate is being increasingly used for the treatment of ectopic pregnancy . Methotrexate is teratogenic for embryos of various species and has been associated with congenital defects . Because methotrexate can be detected in the kidney and liver months after exposure concern has been raised regarding the effects of treatment with high‐dose methotrexate for ectopic pregnancy on subsequent pregnancies.…”
Section: Introductionmentioning
confidence: 99%